2011
DOI: 10.1128/aem.05123-11
|View full text |Cite
|
Sign up to set email alerts
|

Metabolome Profiling Reveals Metabolic Cooperation between Bacillus megaterium and Ketogulonicigenium vulgare during Induced Swarm Motility

Abstract: The metabolic cooperation in the ecosystem of Bacillus megaterium and Ketogulonicigenium vulgare was investigated by cultivating them spatially on a soft agar plate. We found that B. megaterium swarmed in a direction along the trace of K. vulgare on the agar plate. Metabolomics based on gas chromatography coupled with time-of-flight mass spectrometry (GC-TOF-MS) was employed to analyze the interaction mechanism between the two microorganisms. We found that the microorganisms interact by exchanging a number of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(68 citation statements)
references
References 27 publications
3
64
1
Order By: Relevance
“…Recent studies demonstrated that Bacillus sp. could release metabolites in amino acid biosynthesis (Liu et al, 2011a;Zhou et al, 2011) and purine during cell lysis upon sporulation Ma et al, 2011;Zhang et al, 2010), which can be used to compensate the deficient metabolism of K. vulgare (Zou et al, 2012). In this study, our results showed that the blank plasmid did not impair the growth and 2-KLG production in the consortium of K. vulgare-B.…”
Section: Effect Of Overexpression Of Endogenous L-sorbose Pathway On contrasting
confidence: 38%
“…Recent studies demonstrated that Bacillus sp. could release metabolites in amino acid biosynthesis (Liu et al, 2011a;Zhou et al, 2011) and purine during cell lysis upon sporulation Ma et al, 2011;Zhang et al, 2010), which can be used to compensate the deficient metabolism of K. vulgare (Zou et al, 2012). In this study, our results showed that the blank plasmid did not impair the growth and 2-KLG production in the consortium of K. vulgare-B.…”
Section: Effect Of Overexpression Of Endogenous L-sorbose Pathway On contrasting
confidence: 38%
“…The seemingly inconsistent high Mn(II) oxidation rate versus the low relative abundance of QXT-31 suggests the possibility of cooperation with regard to Mn(II) oxidation between QXT-31 and the indigenous microbes. It has been speculated that physical contact (Schroeckh et al, 2009) or metabolic interactions (Zhou et al, 2011) were responsible for this apparent cooperation.…”
Section: Removal Of Organic Pollutants By Qxt-31 and Interaction Of Bmentioning
confidence: 99%
“…Furthermore, Liu et al ( 2011a ) reconstructed the biosynthesis pathways for amino acids in K. vulgare and found out many gaps in the amino acid metabolic pathways, and consequently developed a novel strategy with gelatin supplement, which contains the several kinds of key amino acids that could not be de novo biosynthesized in K. vulgare , and signi fi cantly enhanced the K. vulgare growth and 2-KLG productivity. Zhou et al ( 2011 ) found that the microorganisms interact by exchanging a number of metabolites with time-of-fl ight mass spectrometry. Both intracellular metabolism and cell-cell communication via metabolic cooperation were essential in determining the population dynamics of the ecosystem.…”
Section: Effects Of the Relationship Between Two Bacteria In Mixed Cumentioning
confidence: 99%